THE LANGUAGE OF THE FISH: A STRUCTURAL ANALYSIS OF PISCEAN EXPRESSION - Shoyzokova Aziza Akbar qizi; Nazarova Lobar Farhod qizi; Saparova Sabrina Uchqun qizi; Norqobilova Munisa Otabek qizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article explores the often-overlooked role of individual differences in shaping linguistic expression, with a particular focus on personality archetypes and zodiac-based tendencies. While traditional linguistic analysis emphasizes universal structures of language, it frequently neglects how subjective perception influences communication. This study aims to examine the linguistic features associated with individuals born under the Pisces zodiac sign and to analyze how they construct meaning, express emotions, and interpret discourse across different contexts. The research enters the pseudo-scientific domain of astrology and introduces the concept of astro-linguistics as a framework for understanding symbolic and intuitive modes of communication. The findings suggest that Piscean expression is characterized by indirectness, metaphorical richness, emotional layering, and fluid discourse structures, which distinguish it from more linear and explicit communicative styles. Ultimately, the study argues that language is not only a system of rules but also a reflection of inner perception, sensitivity, and identity.